(untitled) (Feni University Journal, 2026)
In Bangladesh, state-owned commercial banks are the main employers and economic engine. Employee satisfaction and motivation are crucial for boosting the banking industry’s sustainability and productivity. The purpose of this study was to look into how employee happiness in Bangladesh’s state-owned commercial banks was affected by HRM policies. The three state-owned commercial banks in Bangladesh, named Sonali Bank PLC, Janata Bank PLC, and Rupali Bank PLC, made up the study domain. Data was gathered from 202 samples out of the 30,000 total population using the stratified random sampling approach and a structured questionnaire based on a 5-point Likert scale. To gather sample data, only high- and mid-level personnel are taken into consideration. Given the descriptive and analytical character of the study, statistical methods including simple regressions, Cronbach’s alpha, Skewness and Kurtosis test, and descriptive statistics were employed to assess the study hypotheses. According to the study, employee satisfaction at the State-owned Commercial Banks in Bangladesh is significantly impacted by HRM practices (HRM planning and recruitment, training and development, compensation, and performance appraisal at the α≤0.05 level. The findings also demonstrated that the factor that affects employee satisfaction the most is remuneration. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (187-212)